1988
DOI: 10.1007/bf00314350
|View full text |Cite
|
Sign up to set email alerts
|

Bulbocavernosus reflex latencies and somatosensory evoked potentials after pudendal nerve stimulation in the diagnosis of impotence

Abstract: The bulbocavernosus reflex (BCR) was examined in 39 normal potent men and in 252 patients with impaired potency of varying aetiology. For BCR evaluation minimum, maximum and mean latencies, the temporal dispersion in ten successive responses, together with minimum and maximum side differences from simultaneous recordings of the left and right bulbocavernosus muscles were determined. Pathological findings were detected in 125 patients. Somatosensory evoked potentials (SSEPs) recorded from the scalp after stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 29 publications
3
16
1
2
Order By: Relevance
“…With respect to Tackmann et al, 7,8 who reported mean-latencies of 41.7 with a s.d. of 2.8 ms within 30 healthy controls, P1-latency was considered to be normal up to 48.7 ms (mean 2.5 s.d.).…”
Section: Pudendal Nerve Ssepmentioning
confidence: 91%
See 3 more Smart Citations
“…With respect to Tackmann et al, 7,8 who reported mean-latencies of 41.7 with a s.d. of 2.8 ms within 30 healthy controls, P1-latency was considered to be normal up to 48.7 ms (mean 2.5 s.d.).…”
Section: Pudendal Nerve Ssepmentioning
confidence: 91%
“…BCR-latency-measurement was performed according to Tackmann et al 7 with the subject in a supine position. Dorsal penile nerve (DPN) was stimulated electrically by means of ring electrodes applied around the penile shaft, the cathode in the corona glandis and the anode more proximally with a 2±3 cm distance.…”
Section: Bcr-latency-measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially with regards to topographic relations of presumed sites of neurogenic lesions, the possibility to examine selectively the different branches of the pudendal nerve becomes more and more interesting. 9 This will also facilitate a differentiation between central and peripheral lesions. Our interest therefore was focused on evaluation of the diagnostic relevance of penile and perianal pudendal SSEP by direct comparison of the methods.…”
Section: Introductionmentioning
confidence: 99%